Representation of Comfort Meaning in Blibli Home Youtube Ad "Discover Everything at Blibli Home 2022" - Rosyid, Salman Abdul; Apriliani, Riski (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The growing number of Internet users continues to influence e-commerce companies like Blibli in maximizing the use of YouTube as an advertising platform, which is considered efficient and relevant to influence a wide audience's behavior in this era. The aim of this research is to understand how the "Discover Everything at Blibli Home" advertisement represents the meaning of comfort through the aspects of messages and visuals displayed in the ad, and how these elements are utilized to influence the audience on Blibli Home's YouTube ad. The method employed in this study is qualitative, using Roland Barthes' semiotic analysis. The results indicate four aspects representing the meaning of comfort: the physical aspect, the psychospiritual aspect, the environmental aspect, and the social aspect. According to Kotler's consumer behavior factor theory, this study demonstrates that, broadly speaking, the ad uses message and visual elements to represent the meaning of comfort, influencing audience behavior through psychological, personal, and sociocultural factors. "Discover Everything at Blibli Home" employs a postmodernism approach in delivering its message and content, shaping a simulation by utilizing symbolic elements such as color, slogans, product visualization, and intertextuality of popular culture to create hyperreality. This ad not only functions as a means of marketing a product but also as a symbolic construction that creates the desired reality for the audience.